Case report: Co-occurring obsessive-compulsive disorder and affective psychotic disorder complicated by catatonia in an adolescent female patient - To, Wilson; Yung, Crystal; Voss-Hamrick, Tyler; Meacham, Brenner; Freedman, Colin (Frontiers in Psychiatry, 2023)
We present the case of a 16-year-old female patient who experienced the loss of her mother to suicide, leading to post-traumatic stress disorder and prominent mood symptoms. She developed catatonic features during her inpatient psychiatric hospitalization following her own suicide attempt. Over her hospital course, she began to demonstrate signs of co-occurring obsessive-compulsive disorder (OCD) and affective psychotic disorder obfuscated by the severity of her catatonia. After initial workup including neurologic evaluation, laboratory tests, imaging (EEG, MRI), the patient was stabilized on a combination of benzodiazepines, antipsychotics, mood stabilizers, and selective serotonin reuptake inhibitors. The diagnostic challenges of disambiguating multiple concurrent diagnoses in the presence of a syndrome with unclear pathophysiology are discussed. Recommendations are made to thoroughly evaluate thought content during periods of catatonic remission to guide diagnosis and treatment.